Carbon-coated porous Si/C composite anode materials via two-step etching/coating processes for lithium-ion batteries. Issue 17 (1st December 2020) - Hsieh, Cheng-Che; Lin, Yan-Gu; Chiang, Chao-Lung; Liu, Wei-Ren
Abstract: A highly stable Si/SiOx /C composite was synthesized in this study through NaOH etching and carbon-coating approaches for use as an anode material in Li-ion batteries (LIBs). The two-step process not only enhanced the electronic conductivity of the as-synthesized Si/SiOx /C composite by using the two-step etching/coating processes to enhance the columbic efficiency of Si during cycling processes but also architecturally provided an amorphous Si/SiOx composite to buffer volume expansion. The Raman spectroscopy and X-ray diffraction results demonstrate that the etching process involves a transition from crystalline Si to amorphous SiOx . The Fourier transform infrared spectroscopy results further confirm that the vibration mode of Si–O bonding changes from symmetric to asymmetric. The Brunauer–Emmett–Teller analysis reveals that we can control specific surface area and pore-size distribution of NaOH-modified Si by tuning the parameters pertaining to the solid content of Si in NaOH solution. After optimizing the etching and carbon-coating processes, the modified Si/C composite delivered ~780 mAh g −1 for more than 200 cycles at 0.5C, which was better than un-modified one of 315 mAh g −1 after 200 cycles. The results clearly indicate that we could improve cycle stability of Si anode drastically through the NaOH etching process and carbon coating modification. The proposed methodology may provide a potential approach to promoting the synthesis of Si-based anodes for use in the commercial applications of LIBs. Graphical abstract: Image 1